The Concept of Applying Total Quality Management in Improving the Quality of Education - Ade Sofyan; Naf’an Tarihoran; Enung Nugraha (First Ciera Publisher, 2023)
The Indonesian government has made efforts to implement a number of excellent programs to improve the quality of education. However, the variety of challenges faced by schools affects the lack of optimal competition in the quality of education. The purpose of this article is to analyze and describe the concept of Total Quality Management (TQM) as an effort to improve the quality of education. This article uses a qualitative method with a literature review approach. The TQM concept is one of the concepts that can be applied to improve the quality of education. In applying the TQM concept to education, it is necessary to pay attention to several aspects, namely: (1) focus on graduate users, (2) obsession with quality, (3) scientific approach, (4) teamwork, (5) having a long-term commitment and sustainable, (6) continuous improvement efforts, (7) conducting education and training, (8) common perceptions and goals, (9) having a free and controlled organizational culture, and (10) engaging and empowering human resources. All aspects of TQM must be oriented to the education management system, and the behavior of school members, and focus on optimal service in order to meet the needs and desires of the stakeholders.